Analisis Sistem dan Prosedur Pengeluaran Kas Belanja Langsung pada Badan Keuangan dan Aset Daerah Kabupaten Halmahera Utara - Reilin Mare; Dhullo Afandi; I Gede Suwetja (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
Cash disbursement is an important resource component in implementing development programs planned by the government. Cash is recognized at the nominal value of cash or cash equivalents, as well as current accounts with banks whose use is not restricted. The cash disbursement system and procedures consist of 4, namely cash disbursement of inventory money (UP), disbursement of replacement cash inventory (GUP), disbursement of additional reserve money (TUP), and direct cash disbursement (LS). This research aims to analyze whether the system and procedures for disbursing direct cash expenditure at the North Halmahera Regency Regional Financial and Asset Agency are adequate or not. The method used is descriptive qualitative, and data collection through interviews, documentation and observation. The results of the study show that the implementation of the system and procedures for spending direct cash disbursements at BKAD in North Halmahera Regency is in accordance with the regulations in Permendagri No. 77 of 2020 concerning Technical Guidelines for Regional Financial Management, which is implemented through the process of issuing SPD, submitting SPP, issuing SPM, and issuing SP2D . Meanwhile, the internal control system for direct cash disbursements at BKAD North Halmahera Regency as a whole is quite adequate, and in accordance with PP No. 60 of 2008 concerning Government Internal Control Systems (SPIP). However, there is still one element that has not been implemented well, namely control activities, because there is no clear SOP for submitting funding applications. Keywords : Systems, procedures, cash disbursements, direct spending.